JUMLAH KOLONI Streptococcus mutans PADA PLAK GIGI setelahBERKUMUR REBUSAN DAUN SIRIH HIJAU (Piper betle Linn.) - , DEWI SARTIKA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Streptococcus mutans has been identified as the most important bacteria associated with carious lesions. It produces enzymes that convert sucrose into glucan and it also releases lactic acid as a metabolic end result. The leaves of Piper betel Linn contain phenol, cavichol, tannins, and catechins. Previous studies showed that they have antibacterial effect toward Staphylococcus aureus. The aim of this study was to determine the effect of gargling using green betel leaf decoction towards the number of S. mutans colonies in dental plaque. Twenty subjects aged 19 to 23 years was volunteered to join this study. Subjects were divided into control and treatment groups. Control group gargled with distilled water and treatment group gargled with green betel leaf decoction concentration 10%. All subject were undergone scaling and polishing procedure prior the treatment. Subjects were instructed to gargle using 10 ml either distilled water or green betel leaf decoction twice a day for 30 seconds. One mg dental plaques were collected from the surface of maxillary molar before and 5 days after the treatment. The plaque were cultured on TYS20B, a specific media for S.mutans and incubated for 2 days. Streptococcus mutans colonies were identified as white velvety or frosted-glass appearance which grow on the TYS20B. The colonies grown were then counted. The data were analyzed using unpaired student's test. Student's test result showed significantly different between the groups (p<0.05) indicating that gargling using green betel leaf decoction can reduce the risk of caries. In conclusion, gargling using green betel leaf decoction can reduce the number of S.mutans colonies in dental plaque.